CASE STUDY: THE INFLUENCE OF ULTRASOUND AND TENS ON INCREASING THE RANGE OF MOTION OF JOINT IN FROZEN SHOULDER DUE TO ROTATOR CUFF - Susilaningsih, Endang; Rahman, Farid (Academic Physiotherapy Conference Proceeding, 2021)
Frozen shoulder is a disorder of the shoulder joint that causes pain and always causes limitation of joint motion in all directions resulting in physical problems and decreased functional activity. Frozen Shoulder due to rotator cuff is caused by inflammation from prolonged tendinitis, characterized by a marked limitation of the glenohumeral joint range of motion, both active and passive. The prevalence of this disease is about 20% of the general population and 10-20% in people with diabetes (Shichling & Walsh, 2001). And often occurs in people above 40 years of age, especially for women aged 50 years. When trauma occurs, it causes a local inflammatory reaction in the joints and causes adhesions to the joint capsule and cartilage, which is characterized by shoulder pain that occurs gradually, sharper pain, stiffness and limitation of motion. Frozen shoulder can be treated with medication and a physiotherapy program. Physiotherapy programs are useful for reducing pain, both pressure and motion, increasing muscle strength, increasing the range of motion of the joints and restoring functional activities/daily activities. The purpose of this study was to determine the effectiveness of the physiotherapy program with Ultrasound, TENS, and Codman Pendular exercise.